THE EFFECT OF PROFITABILITY, CAPITAL STRUCTURE, ASSET STRUCTURE, AND FIRM AGE ON FIRM VALUE - Harsono, Serena Beatrice; Susanto, Liana (Graduate Program of Universitas Tarumanagara, 2023)
The goal of this study was to gather empirical data on how firm value in manufacturing enterprises is impacted by factors such as profitability, capital structure, asset structure, and firm age. In this study, 89 manufacturing businesses that were listed on the Indonesia Stock Exchange between 2018 and 2020 are used as a sample. The sample selection used purposive sampling method and obtained a sample of 89 companies. The EViews 10 program was used to process the data for this investigation. The findings of this study suggest that firm value is significantly positively influenced by profitability and capital structure. Asset composition has no significant impact on firm value. Firm age has a significant negative effect on firm value. This research is expected to provide benefits for investors by increasing knowledge about company values and is expected to be used as consideration in making investment decisions to visualize company assets so that investors can achieve the expected returns.